Assessment of oil change intervals in urban buses based on the selected physicochemical properties of used engine oils - Gołębiowski, Wojciech; Zając, Grzegorz; Sejkorová, Marie; Wolak, Artur (My University, 2024)
The paper presents the results of the analysis of selected physicochemical parameters of engine oils after their use. The oils were obtained both from urban buses belonging to the fleet of a municipal transport company in Lublin, Poland but also from the city of Pardubice in the Czech Republic. Five samples of 10W40 semi-synthetic oil and four samples of 5W30 synthetic oil were tested. Kinematic viscosity at 40°C and 100°C, oxidation, nitration, sulfonation, total acid number (TAN), total base number (TBN), remaining antiwear additives, water content and glycol content, were assessed using infrared spectroscopy (FTIR). The tests were performed on the basis of the ASTM E2412-10 standard. The article also presents the exceedance of the limit values results for the selected parameters. The results of the research can be used in optimizing the engine oil change interval so that the decision to replace the oil is justified both in economic and technical terms, taking into account the need to maintain the service life of the bus. © 2024, Polish Scientific Society of Combustion Engines. All rights reserved.
Posouzení intervalů výměny olejů v městských autobusech na základě vybraných fyzikálně-chemických vlastností použitých motorových olejů
Keywords: degradation; engine oil; FTIR; oil change; urban buses; degradace; motorový olej; FTIR; výměna oleje; městské autobusy